2005
DOI: 10.1039/b501259g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ordered mesoporous carbons with channel structure from an organic–organic nanocomposite

Abstract: Mesoporous carbons with ordered channel structure (COU-1) have been successfully fabricated via a direct carbonization of an organic-organic nanocomposite.The discovery of nanostructured carbon materials such as fullerenes 1 and carbon nanotubes 2 has led to a considerable interest in the development of various carbonaceous materials. In particular, porous carbonaceous materials have been attracting much attention because of their high surface areas, large pore volumes, chemical inertness and high mechanical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
352
0
12

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 532 publications
(371 citation statements)
references
References 16 publications
7
352
0
12
Order By: Relevance
“…Electron microscopy images of the carbon film are shown in Figure 9. Similar results were reported by Tanaka et al (84), in which the same carbon precursor and Pluronic F127 (E0 10 6P07oE0 10 6) were used for organic-organic self-assembly ( Figure 10). Triethyl orthoacetate (EOA) was added as a carbon co-precursor.…”
Section: Surfactant Self-assembly Approachsupporting
confidence: 78%
“…Electron microscopy images of the carbon film are shown in Figure 9. Similar results were reported by Tanaka et al (84), in which the same carbon precursor and Pluronic F127 (E0 10 6P07oE0 10 6) were used for organic-organic self-assembly ( Figure 10). Triethyl orthoacetate (EOA) was added as a carbon co-precursor.…”
Section: Surfactant Self-assembly Approachsupporting
confidence: 78%
“…Tanaka et al demonstrated that the common and cheap Pluronic triblock-copolymer PEO-b-PPO-b-PEO can also template mesoporous carbon. 44 They employed Pluronic F127 as a template, resorcinol-formaldehyde ''RF'' as a carbon precursor, and triethyl orthoacetate (EOA) as a co-precursor. EOA served two purposes; it increased the carbon content of the final material and significantly enhanced the ordering of the porous structures.…”
Section: 43mentioning
confidence: 99%
“…Along with the development of nanocarbon science, more and more novel nanostructured carbon materials have been adopted as new support materials, and have already shown much better loading effect because of their unique nanostructure. [3][4][5][6][7] Among the reported nanocarbon supports, ordered mesoporous carbons (OMCs) are especially impressive, and are attracting increasing scientific interests due to their unusual physical and chemical characteristics, such as ordered and tailored nanostructure, high surface area, large pore volume, narrow pore size distribution in the mesopore range, high controlled pore surface chemistry, good electrical conductivity and so on. [5][6][7][8][9][10][11] Joo et al have firstly reported that an OMC with a highly ordered hexagonal array of nanoporous carbons, CMK-5, supported a high dispersion of Pt nanoparticles (<3 nm), exceeding that of many common microporous carbon materials, which gave rise to a promising electrocatalytic activity for oxygen reduction reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] Among the reported nanocarbon supports, ordered mesoporous carbons (OMCs) are especially impressive, and are attracting increasing scientific interests due to their unusual physical and chemical characteristics, such as ordered and tailored nanostructure, high surface area, large pore volume, narrow pore size distribution in the mesopore range, high controlled pore surface chemistry, good electrical conductivity and so on. [5][6][7][8][9][10][11] Joo et al have firstly reported that an OMC with a highly ordered hexagonal array of nanoporous carbons, CMK-5, supported a high dispersion of Pt nanoparticles (<3 nm), exceeding that of many common microporous carbon materials, which gave rise to a promising electrocatalytic activity for oxygen reduction reaction. 8 Calvillo et al have adopted a functionalized OMC with a highly ordered hexagonal array of carbon nanorods, CMK-3, to support Pt nanoparticles, and the as-prepared catalyst showed improved catalytic performance for methanol electrooxidation in comparison with Vulcan XC-72 carbon black.…”
Section: Introductionmentioning
confidence: 99%